Cantilever-based micro thrust measurement and pressure field distribution of biomimetic robot fish actuated by macro fiber composites (MFCs) actuators. (29th January 2021) - Meng, Haofeng; Lou, Junqiang; Chen, Tehuan; Xu, Chao; Chen, Hairong; Yang, Yiling; Cui, Yuguo
Abstract: Underwater autonomous vehicles (UAVs) actuated by smart actuators have attracted increasing attention. A miniature macro fiber composite (MFC)-actuated robot fish inspired by koi fish is developed. A cantilever mechanism is designed to transfer the dynamic micro thrust of the robot fish. Three design indexes, namely the bending stiffness, the ratio of the bending stiffness to the torsional stiffness, and the natural frequency of the cantilever transducer are proposed. Thus, a simple and effective method to determine the structural parameters of the cantilever-based micro thrust force measurement system is presented. Calibration results demonstrated that the parameters of the proposed cantilever transducer match well with the designed indexes. Dynamic variation mechanisms of the micro thrust force associated with the swimming behaviors of the robot fish are well captured using the proposed measurement system. Experimental results show that the MFC-actuated robot fish obtains the biggest mean thrust of 1.73 mN in the case of the largest oscillating velocity. The maximum instant thrust grows with the increment of the oscillating frequency, and achieves its maximum of 7.35 mN in the case of 10 Hz. While the maximum instant drag first decreases then increases as the actuation frequency increases, and obtains its minimum of −2.62 mN in the case of the maximum oscillating velocity. On the contrary, variations of the thrust pattern/oscillating period are reversed to those of the maximum instant drag. Computational fluid dynamics results demonstrate that variations of the instant thrust are fully determined by the distribution and intensity of the concentrated pressure regions induced by the oscillating caudal fin. The cycle-averaged velocity fields are closely related to the mean thrust generated by the MFC-actuated robot fish. As a result, the fluid–structure interaction mechanisms associated with the thrust variations of the MFC-actuated robot fish are revealed. This study may be useful for the design and realization of UAVs actuated by smart actuators.